Development of IoT system for hybrid hydrokinetic and wind energy harnessing - Muhammad Luqman Hakim, Zahir Shah (2022)
In this project, the Io T system for hybrid hydrokinetic and wind energy for portable energy harnessing devices has been proposed. Hybrid hydrokinetic and wind is an alternative technology to generate electricity through wind and water energy. In this project, the hybrid hydrokinetic energy and wind energy has been designed to be used in both water and wind condition. However, some issues need to consider such as, the suitable size and the mobility for the turbine must be considered, the low extraction of fluctuation and wind speed and inaccessibility to monitor the status of devices. The blynk application is used to monitor the voltage and current value. Although the sensors have been monitored, the ESP3 2 must be used to read the sensor value and send the data to blynk application. For the results, the IoT system for this project has been achieved its target. The system can monitor both current and voltage sensors only using a mobile phone.